Delivery of nitric oxide with a nanocarrier promotes tumour vessel normalization and potentiates anti-cancer therapies - Sung, Yun-Chieh; Jin, Pei-Ru; Chu, Li-An; Hsu, Fu-Fei; Wang, Mei-Ren; Chang, Chih-Chun; Chiou, Show-Jen; Qiu, Jiantai Timothy; Gao, Dong-Yu; Lin, Chu-Chi; Chen, Yu-Sing; Hsu, Yi-Chiung; et al. (Nature nanotechnology, 2019)
Abnormal tumour vasculature has a significant impact on tumour progression and response to therapy. Nitric oxide (NO) regulates angiogenesis and maintains vascular homeostasis and, thus, can be delivered to normalize tumour vasculature. However, a NO-delivery system with a prolonged half-life and a sustained release mechanism is currently lacking. Here we report the development of NanoNO, a nanoscale carrier that enables sustained NO release to efficiently deliver NO into hepatocellular carcinoma. Low-dose NanoNO normalizes tumour vessels and improves the delivery and effectiveness of chemotherapeutics and tumour necrosis factor-related, apoptosis-inducing, ligand-based therapy in both primary tumours and metastases. Furthermore, low-dose NanoNO reprogrammes the immunosuppressive tumour microenvironment toward an immunostimulatory phenotype, thereby improving the efficacy of cancer vaccine immunotherapy. Our findings demonstrate the ability of nanoscale NO delivery to efficiently reprogramme tumour vasculature and immune microenvironments to overcome resistance to cancer therapy, resulting in a therapeutic benefit.